An Introduction to Behavioural Ecology - Davies, Nicholas B. (New York Academy of Sciences Ser., 2012)
This textbook helped to define the field of Behavioural Ecology. In this fourth edition the text has been completely revised, with new chapters and many new illustrations and full colour photographs. The theme, once again, is the influence of natural selection on behaviour -- an animal's struggle to survive and reproduce by exploiting and competing for resources, avoiding predators, selecting mates and caring for offspring, -- and how animal societies reflect both cooperation and conflict among individuals. -- Provided by publisher.